DEVELOPMENT OF RESISTANCE-BASED ARCHERY TRAINING MODELS FOR ATHLETES AGED 13-15 YEARS - Devi Syah Putra Syahputra; Ramdan Pelana; Hernawan (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
The purpose of this study was to produce a resistance-based archery training model for athletes aged 13-15 years. The method used in this research is Research and Development. The study was conducted at DSR Archery Club Depok City and the research subjects were athletes aged 13-15 years. This research begins with needs analysis, product planning, development, implementation and evaluation. The instruments used were the 30 M Archery Test in the sport of archery, an analysis of the need for in-depth interviews to coaches at the archery club and an assessment questionnaire to experts to test the validity of variations in the training model. Based on research data consisting of needs analysis, product design, expert validation, small and large group trials, and effectiveness tests. The conclusion is first, resistance-based archery training model for athletes aged 13-15 years can be developed and applied in training archery skills and muscle strength training. Second, the exercise model developed based on research data obtained effective results for athletes aged 13-15 years